Nurses' Knowledge about Diabetes Foot Ulcer Prevention and Treatment: An Integrative Review - Hasdi, Hasdi; Syahrul, Syahrul; Yusuf, Saldy (Indonesian Contemporary Nursing Journal (ICON Journal), 2022)
Introduction: Diabetic Foot Ulcer (DFU) is a complication often experienced by patients with Diabetes Mellitus (DM). Evidence-based prevention and treatment in DM patients who are at risk of DFU can reduce the global economic burden. Nurses' knowledge plays an important role in screening, prevention, and proper treatment of DFU. This review identifies evidence of nurses' knowledge about the prevention and treatment of DFU and identify factors related to nurses' knowledge. Method: The study applied an integrative review design. The relevant literature were searched from PubMed, CINAHL (EBSCO), Wiley Online Library, ScienceDirect, and ProQuest. The inclusion criteria was articles published in English, peer-reviewed articles, and journals between January 2016 and May 2021, by using keywords; “nurs*”, “diabetic foot*” “knowledge”, "awareness" and "perception". Result: There are 10 articles met the inclusion criteria and eligible to review. Nurses have low knowledge about diabetic foot care and also have limited knowledge about the characteristics and complications of DFU. Factors related to nurses' knowledge about DFU prevention and treatment; training, educational qualifications, work experience, educational institutions, and age. Conclusion: This review revealed that nurses experienced a significant knowledge deficit in several aspects regarding the prevention and treatment of DFU. So that new effective education and training must be developed to address the knowledge gap, one of which is the online training method utilizing telenursing-based electronic learning (e-learning).